2018
DOI: 10.1002/marc.201800145
|View full text |Cite
|
Sign up to set email alerts
|

Precision Polyelectrolytes with Phenylsulfonic Acid Branches at Every Five Carbons

Abstract: A precision polyethylene containing phenyl branches at every fifth carbon (p5Ph) is nearly quantitatively functionalized (≈95%) with sulfonic acid groups on the para-position of each phenyl branch (p5PhS-H). Unlike polystyrene sulfonate (PSS), p5PhS-H has a glass transition temperature (T = 109 °C) well below its thermal decomposition temperature (T ≈ 200 °C), making this new material capable of thermal processing into molds and films at temperatures between these thermal limits. Neutralization of the sulfonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(44 citation statements)
references
References 28 publications
2
42
0
Order By: Relevance
“…1,3,12 All of these are important factors we must consider when designing new polymeric PEMs. 13 This study focuses on a novel linear polyethylene with an atactic phenylsulfonic acid pendant group precisely spaced on every 5 th carbon, p5PhSA, Figure 1. This polymer was previously synthesized through ring-opening metathesis polymerization (ROMP) of 4phenylcyclopentene (4PCP), followed by mild hydrogenation of the backbone olefins (> 99%), and sulfonation of the phenyl rings (95%).…”
Section: Introductionmentioning
confidence: 99%
“…1,3,12 All of these are important factors we must consider when designing new polymeric PEMs. 13 This study focuses on a novel linear polyethylene with an atactic phenylsulfonic acid pendant group precisely spaced on every 5 th carbon, p5PhSA, Figure 1. This polymer was previously synthesized through ring-opening metathesis polymerization (ROMP) of 4phenylcyclopentene (4PCP), followed by mild hydrogenation of the backbone olefins (> 99%), and sulfonation of the phenyl rings (95%).…”
Section: Introductionmentioning
confidence: 99%
“…Details of the synthesis of p 5PhS‐Li have been previously reported. [ 21 ] For the specific material reported herein, the parent polymer, p 5Ph, was determined to have a number averaged molar mass ( M n ) of 17 kg mol −1 and a dispersity ( Đ ) of 1.67 via size exclusion chromatography. Full synthesis and characterization details are provided in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…In prior work, it was shown that the sulfonation and neutralization procedure is not deleterious to the molar mass and dispersity of the parent polymer. [ 21 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-polymerization functionalization represents one approach to introduce charged moieties, ranging from statistical 16 to periodic 17 arrangements. Alternatively, statistical copolymerization of distinct charged and uncharged monomers remains a facile strategy to construct sequencepolydisperse designer polyelectrolytes.…”
Section: Introductionmentioning
confidence: 99%